A year down yonder - Peck, Richard, 1934- (New York : Dial Books for Young Readers, 2004)
During the recession of 1937, fifteen year-old Mary Alice is sent to live with her feisty, lager-than-life grandmother in rural illinois and comes to a better understanding of this fearsome woman.
Newbery Medal, 2001
Keywords: Grandmothers -- Fiction; Contry life -- Illinois -- Fiction; Illinois -- Fiction